51.6k views
8 votes
Help !!!
See question in image.
Please show workings .
​​

Help !!! See question in image. Please show workings . ​​-example-1

1 Answer

10 votes

Answer:


(dy)/(dx) = 2x + 3

Explanation:

The gradient function is the derivative
(dy)/(dx)

Differentiate using the power rule


(d)/(dx) (a
x^(n) ) = na
x^(n-1) and
(d)/(dx) ( constant ) = 0

Given

y = x² + 3x + 1, then


(dy)/(dx) = 2
x^(2-1) + 3
x^(1-1) + 0 = 2x + 3
x^(0) = 2x + 3 ← gradient function

User JuanF
by
5.9k points